1) The given equation can be written as "\\frac{dy}{dx}=-\\frac{(x-y+1)}{(x+4y+1)}" ......(1)
Here the two lines "x-y+1=0" and "x+4y+1=0" intersect at the point "(-1,0)" .
We now transfer the origin by putting "x=-1+X," "y=0+Y" ......(2)
This gives "dx=dX" and "dy=dY"
Therefore from (1) , we get "\\frac{dY}{dX}=-\\frac{(X-Y)}{(X+4Y)}" ........(3)
Put "Y=vX." Then the equation (3) becomes
"v+X.\\frac{dv}{dX}=-\\frac{(1-v)}{(1+4v)}"
"\\implies X.\\frac{dv}{dX}=-\\frac{(1-v)}{(1+4v)}-v"
"\\implies X.\\frac{dv}{dX}=-\\frac{(1+4v^2)}{(1+4v)}"
Separating the variables, we get
"\\frac{(1+4v)}{(1+4v^2)}dv+\\frac{dX}{X}=0"
Now integrating we get,
"\\intop\\frac{(1+4v)}{(1+4v^2)}dv+\\intop \\frac{dX}{X}=0"
"\\implies \\intop\\frac{1}{(1+4v^2)}dv+\\intop\\frac{4v}{(1+4v^2)}dv+\\intop \\frac{dX}{X}=0"
"\\implies \\frac {1}{2}.tan^{-1}(2v)+\\frac{1}{2}.log|4v^2+1|+log|X|=log|c|" "["where "log|c|" is an integrating constant"]"
"\\implies tan^{-1}(2v)+log|4v^2+1|+2log|X|=2log|c|"
"\\implies \\tan^{-1}(2.\\frac{Y}{X})+log|\\frac{4Y^2+X^2}{X^2}|+log|X|^2=log|c|^2" [Putting the value of "v=\\frac{Y}{X}"]
"\\implies \\tan^{-1}(2.\\frac{Y}{X})+log|{4Y^2+X^2}|-log|{X^2}|+log|X|^2=log|c|^2"
"\\implies \\tan^{-1}(2.\\frac{Y}{X})+log|{4Y^2+X^2}|=K(say)"
"\\implies \\tan^{-1}(\\frac{2y}{x+1})+log|{4y^2+(x+1)^2}|=K" [ Putting the value "X=x+1" and "Y=y" ]
Which is the required solution.
2) Here the two lines "6x-3y+2=0" and "2x-y-1=0" are parallel.
We see that the given equation may be written as "\\frac{dy}{dx}=-[\\frac{3(2x-y)+2}{(2x-y)-1}]." ........(1)
Put "2x-y=v" in (1) , so that "\\frac{dv}{dx}=2-\\frac{dy}{dx}"
Hence we obtain from (1), "2-\\frac{dv}{dx}=-[\\frac{3v+2}{v-1}]"
"\\implies \\frac{dv}{dx}=[\\frac{3v+2}{v-1}]+2"
"\\implies \\frac{dv}{dx}=[\\frac{5v}{v-1}]"
Separating the variables we get , "\\frac{v-1}{5v}dv=dx" .......(2)
Now integrating (2) we have , "\\intop \\frac{v-1}{5v}dv=\\intop dx"
"\\implies \\frac{1}{5}\\intop dv- \\frac{1}{5}\\intop \\frac{1}{v}dv=\\intop dx"
"\\implies \\frac{1}{5}v-\\frac{1}{5}log|v|=x+C" [where "C" is an integrating constant]
"\\implies v-log|v|=5x+5C"
"\\implies (2x-y)-log|2x-y|=5x+5C" [ Putting "v=2x-y" ]
"\\implies log|2x-y|+(3x+y)=K" (say)
Which is the required solution.
Comments
Leave a comment